Pengaruh Konsentrasi dan Lama Perendaman Larutan Kalium Hidroksida Terhadap Pematahan Dormansi Calon Benih Tanaman Padi (Oryza sativa L.) - Mifthahul Huda; Asih Farmia; Siwitri Munambar (Universitas Sebelas Maret, 2022)
This study aimed to determining the effect of potassium hydroxide solution concentration, soaking time, and the interaction of the two on the breaking dormancy of prospective rice seeds (Oryza sativa L.). The research was conducted in February to April at the Seed Laboratory of Polbangtan Yogyakarta, Magelang, and the UPTD of the Barongan Agricultural Seed Center, Bantul Regency. This study was a factorial experiment (3 x 3) + 1 control arranged in a completely randomized design. Factor I in the form of potassium hydroxide concentration with 3 treatment levels and factor II in the form of soaking time with 3 treatment levels. In total there were 9 treatment combinations with one control which was repeated 3 times. The variables observed included maximum growth potential, germination capacity, growth speed, and growth simultaneously. Observational data were analyzed using variance (ANOVA) and if it was known that there was a significant effect, it was continued using the 5% DMRT test. The results showed that a concentration of 0.1% gave more optimal results in increasing maximum growth potential, germination, growth speed, and growing simultaneously. The immersion time On the other hand, the 36 hours showed more optimal results in increasing maximum growth potential, germination, growth speed, and growing simultaneously. Meanwhile, the best treatment combination was the combination of 0.1 potassium hydroxide solution concentration and 36 hours of soaking time which could increase the maximum growth potential, germination, and simultaneous growth of the Ciherang variety of rice seed candidates.